MENGATASI AUDIT DELAY MELALUI HUBUNGAN KORELASIONAL TOTAL ASET DAN KUALITAS AUDITOR - William Sitorus; Rolyana Ferinia Pintauli (Jurnal Ekonomis, 2022)
This study aims to determine the effect of total assets and audit quality on audit delays in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The type of research used is quantitative research. This study used secondary data from the Indonesia Stock Exchange. The population in this study is a manufacturing company in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 30 companies. The sampling technique uses a purposive sampling technique. The samples obtained were 27 companies so with observations for three years the total sample was 81. The analysis methods used are Descriptive statistical analysis, multiple Linear Regression, Hypothesis Testing (Correlation Coefficient Test and Coefficient of Determination), and Model feasibility (Statistics f and Statistical t)). The results of this study show that Total Assets do not affect Audit Delay, Auditor Quality affects Audit Delay, and Total Assets and Auditor Quality together affect Audit Delay in manufacturing companies listed on the IDX in 2019-2021. Keywords: Total Assets, Audit Quality, Audit Delay